2023
DOI: 10.3390/molecules28093730
|View full text |Cite
|
Sign up to set email alerts
|

Armeria maritima (Mill.) Willd. Flower Hydromethanolic Extract for Cucurbitaceae Fungal Diseases Control

Abstract: The cliff rose (Armeria maritima), like other halophytes, has a phenolics-based antioxidant system that allows it to grow in saline habitats. Provided that antioxidant properties are usually accompanied by antimicrobial activity, in this study we investigated the phytochemicals present in a hydromethanolic extract of A. maritima flowers and explored its antifungal potential. The main phytocompounds, identified by gas chromatography–mass spectrometry, were: hexadecanoic acid, octadecanoic acid, 9-octadecenoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…and Perry, and Origanum syriacum L. (600 µg•mL −1 ) [78,79,82], and it is comparable to that of Silene uniflora Roth (1000 µg•mL −1 ) [73]. Against F. oxysporum spp., the activity is lower than those of Cestrum nocturnum L. ethyl acetate and methanol extracts (500 µg•mL −1 ) [89] and A. maritima extract (750 µg•mL −1 ) [44], and it is comparable to that of Cestrum nocturnum hexane and chloroform extracts (1000 µg•mL −1 ) [89]. As for S. sclerotiorum, higher activities have only been reported for A. maritima (375 µg•mL −1 ) [44] and for some C. nocturnum extracts (250-1000 µg•mL −1 ) [89], and a comparable activity has been reported for Zingiber officinale Roscoe essential oil (1000 µg•mL −1 ) [100].…”
Section: On the Efficacy Of Other Natural Compounds Against The Phyto...mentioning
confidence: 77%
See 2 more Smart Citations
“…and Perry, and Origanum syriacum L. (600 µg•mL −1 ) [78,79,82], and it is comparable to that of Silene uniflora Roth (1000 µg•mL −1 ) [73]. Against F. oxysporum spp., the activity is lower than those of Cestrum nocturnum L. ethyl acetate and methanol extracts (500 µg•mL −1 ) [89] and A. maritima extract (750 µg•mL −1 ) [44], and it is comparable to that of Cestrum nocturnum hexane and chloroform extracts (1000 µg•mL −1 ) [89]. As for S. sclerotiorum, higher activities have only been reported for A. maritima (375 µg•mL −1 ) [44] and for some C. nocturnum extracts (250-1000 µg•mL −1 ) [89], and a comparable activity has been reported for Zingiber officinale Roscoe essential oil (1000 µg•mL −1 ) [100].…”
Section: On the Efficacy Of Other Natural Compounds Against The Phyto...mentioning
confidence: 77%
“…When comparing the efficacy of E. serrata extract against other plant extracts tested against the four phytopathogens considered here (Table S1) [24,44,, it may be observed that the MIC values (750 µg•mL −1 against P. cichorii and 1000 µg•mL −1 against the three fungal taxa) are among the lowest reported to date. The antibacterial activity against P. cichorii is the highest among the plant extracts presented in Table S1, comparable to that of Ginkgo biloba L. [24].…”
Section: On the Efficacy Of Other Natural Compounds Against The Phyto...mentioning
confidence: 91%
See 1 more Smart Citation
“…Willd. [ 28 ], Taxus baccata L. [ 29 ], and in small amounts in pomegranates, peas, cabbages [ 30 ], Foeniculum vulgare Mill. [ 31 ], and Landolphia owariensis Beauv.…”
Section: Discussionmentioning
confidence: 99%
“…A more extensive comparison with the effectiveness of other tested plant extracts against the six fungi studied herein can be found in Table S1 [23,24,33,. However, caution should be exercised in comparing the results due to variations in isolates (or species, in the case of the genus Colletotrichum) across different studies.…”
Section: Comparison Of Efficacy Vs Other Plant Extractsmentioning
confidence: 99%